The rise of the individual in 1950s Israel : a challenge to collectivism / Orit Rozin ; translated by Haim Watzman. - Rozin, Orit (The Schusterman series in Israel studies, 2011)
A provocative history of Israeli society in the 1950s that demonstrates how a voluntarist collectivism gave way to an individualist ethos.